Strategi Pengembangan Penulisan Karya Ilmiah pada Guru di Kabupaten Sidoarjo - Dewie Tri Wijayati Wardoyo; Achmad Kautsar; Hujjatullah Fazlurrahman (Abimanyu : Jornal of Community Engagement, 2020)
Every teacher is obliged to carry out various activities in carrying out his duties and responsibilities. The scope of the teacher's activities includes (1) attending education, (2) handling the learning process, (3) conducting professional development activities and (4) supporting activities. The two partners of this activity have the same problem, namely, the teachers still have difficulty in making scientific papers. Whereas professional teachers expect to be able to pursue a career with scientific work for promotion. When viewed from the facts in the field (both partners), only 20% of teachers can write good scientific work.Methods of training, mentoring and monitoring to resolve partner issues that have been mutually agreed upon and stages in achieving the solutions offered to overcome the main problems of partners in the period of program realization. In the initial conditions before the training, only 7 teachers had PTK designs, but after training and mentoring, there were 20 teachers who drafted PTK proposals, the remaining 5 were still constrained.